Mitigación del isi (interferencia intersimbólica) sobre un sistema wimax fijo - Floreano Tumbaco, Byron Alberto (2010)
This article discusses possible solutions to mitigate the different types of fainting that occur in a multipath channel, which will be chosen for a specific scenario Fixed WiMAX system, where the main problem is to eliminate the ISI with the help of theoretical analysis and then implement optimal solutions, where we only focus on two solutions to be implemented in a software simulation using basic elements for a wireless communication system based on an OFDM system, which takes advantage of using the FFT / IFFT, also the data will be modulated and demodulated in 16QAM and 32QAM, to finally make a comparison between the data sent with data received at the output of the system, in order to obtain a measurement as is the bit error rate and finally draw conclusions from our analysis concerned.